2006
DOI: 10.1180/0026461067060356
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in gem corundum characteristics, eastern Australian basaltic fields: trace elements, fluid/melt inclusions and oxygen isotopes

Abstract: Corundum xenocrysts from alkaline basalt fields differ in characteristics and hence lithospheric origins. Trace element, fluid/melt inclusion and oxygen isotope studies on two eastern Australian corundum deposits are compared to consider their origins. Sapphires from Weldborough, NE Tasmania, are magmatic (high-Ga, av. 200 ppm) and dominated by Fe (av. 3300 ppm) and variable Ti (av. 400 ppm) as chromophores. They contain Cl, Fe, Ga, Ti and CO 2 -rich fluid inclusions and give d 18 O values (5.1À6.2%) of mantle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 39 publications
4
27
0
Order By: Relevance
“…Sutherland et al 2002Sutherland et al , 2009Garnier et al 2005;Zaw et al 2006;Peucat et al 2007). Generally, Fe and Ga reveal higher concentrations in magmatic sapphires (~1800 to 13,000 ppm Fe and ~70 to 570 ppm Ga), than in metamorphic ones which have Fe and Ga contents less than 3000 and 75 ppm, respectively.…”
Section: Composition Of Sapphires: Magmatic Versus Metamorphic Originmentioning
confidence: 99%
See 2 more Smart Citations
“…Sutherland et al 2002Sutherland et al , 2009Garnier et al 2005;Zaw et al 2006;Peucat et al 2007). Generally, Fe and Ga reveal higher concentrations in magmatic sapphires (~1800 to 13,000 ppm Fe and ~70 to 570 ppm Ga), than in metamorphic ones which have Fe and Ga contents less than 3000 and 75 ppm, respectively.…”
Section: Composition Of Sapphires: Magmatic Versus Metamorphic Originmentioning
confidence: 99%
“…The 18 O value in gem corundum represents a useful tool for deciphering its geological origin (Yui et al 2003Giuliani et al 2005Giuliani et al , 2007Giuliani et al , 2009Garnier et al 2005;Zaw et al 2006;Sutherland et al 2009). As the mantle and crustal rocks show distinct oxygen isotope compositions, the 18 O value enables us to investigate the origin and source of corundum.…”
Section: Oxygen Isotopes Of Sapphirementioning
confidence: 99%
See 1 more Smart Citation
“…Most authors (e.g., Sutherland et al 1998b) relate the HFSE enrichment of the sapphires and the presence of Columbite Group, Pyrochlore Group and of Nb-rich rutile mineral inclusions to highly evolved SiO 2 undersaturated silicate melts such as syenites, or nepheline syenites. A further observation leading these authors to favor syenites as parental melts is that repeatedly melt inclusions of syenitic composition were reported from magmatic sapphires (e.g., Pakhomova et al 2006;Zaw et al 2006;Izokh et al 2010). Up until now, carbonatites have not been considered as potential parental melts, although many authors (e.g., Coenraads et al 1990;Van Long et al 2004;McGee 2005;Nechaev et al 2009;Izokh et al 2010;Palke et al 2017) reported that CO 2 must have played a significant role in the formation of these sapphires, as CO 2 -rich fluid inclusions are commonly observed in many magmatic sapphires.…”
Section: Constraints On the Parental Meltmentioning
confidence: 99%
“…The zircon found in the stream sediments are weakly translucent and multicolored, showing yellow to brownish tints and, in places, achieve jeweler's quality. Detrital zircon of this type were also observed in alkaline basalts in NSW, Australia, Thailand, Vietnam, Cambodia and Saxony, Germany, where zircon is also associated with sapphire of gem quality (Garnier et al, 2005;Tröger and Seifert, 1963;Zaw et al, 2006). In the chessboard classification scheme sensu Dill (2010) this type of deposit has been categorized as 39B, zircon-sapphire deposits within alkaline basalts.…”
Section: Morphology Of Zircon and Its Originmentioning
confidence: 93%